2023
DOI: 10.1246/bcsj.20230093
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous Carbon Materials from Terminalia bellirica Seed for Iodine and Methylene Blue Adsorption and High-Performance Supercapacitor Applications

Abstract: Here we report the methylene blue adsorption and energy storage supercapacitance performances of the nanoporous activated carbons obtained by the zinc chloride (ZnCl2) activation of biowaste, Terminalia bellirica (Barro) seed stone. The activation was performed at lower temperatures (400–700 °C) under an inert nitrogen gas atmosphere. The total specific surface area and pore volume range from 1077 to 1303 m2 g−1 and 0.752 to 0.873 cm3 g−1, depending on the carbonization temperature. Due to the well-developed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…The GCD results show that the reference sample HrP_500 shows the shortest discharge time indicating a poor specific capacitance, which can be attributed to the lack of porosity, whereas HrC_Z700 has optimal surface area and porosity and gives the longest discharge time, confirming a maximum charge storage capacity based on its well-developed nanoporous structure. The specific capacitance (Cs) of HrC_Z700 calculated using Equation (1) at 1 A g −1 is 328.6 F g −1 , which is higher than that of other carbon materials derived from different biomass (Table S1) [12,14,16,33,36,39,. For other electrodes, values of C s were calculated to be ca.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…The GCD results show that the reference sample HrP_500 shows the shortest discharge time indicating a poor specific capacitance, which can be attributed to the lack of porosity, whereas HrC_Z700 has optimal surface area and porosity and gives the longest discharge time, confirming a maximum charge storage capacity based on its well-developed nanoporous structure. The specific capacitance (Cs) of HrC_Z700 calculated using Equation (1) at 1 A g −1 is 328.6 F g −1 , which is higher than that of other carbon materials derived from different biomass (Table S1) [12,14,16,33,36,39,. For other electrodes, values of C s were calculated to be ca.…”
Section: Resultsmentioning
confidence: 82%
“…Supercapacitors, which are commonly referred to as electrical double-layer capacitors (EDLCs), can be used as electrochemical energy devices that accumulate charge in the form of an electrochemical double-layer at the interface between an electrolyte solution and an electrode surface. Activated nanoporous carbon prepared from biomass has been widely applied for supercapacitor electrode applications based on their ultrahigh surface areas, well-developed pore size distributions, low costs, simple preparation methods, excellent electrical conductivity, and high physicochemical stability [11][12][13][14][15][16][17][18][19][20]. The specific surface area and the porous structure are key factors in the use of carbon materials as electrodes since their optimization can be used to enhance the specific capacitance [21].…”
Section: Introductionmentioning
confidence: 99%
“…Even today, the development of various functional materials is still necessary to meet the demands of energy [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ], the environment [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], and biomedical requirements [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Modern science and technology must develop materials for various functions, such as for energy production [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ], energy storage [ 46 , 47 , 48 , 49 , 50 , 51 , 52 ], separation [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , …”
Section: Introductionmentioning
confidence: 99%
“…A previous work demonstrated that zinc chloride AC from amla seeds, barro and harro seeds showed the necessary characterization suitable for an electrode material of a supercapacitor [11,12,13]. In contrast, there was no literature in the use of phosporic acid as an activating agent for harro and amla seeds even though the phosphoric acid is environmentally friendly.…”
Section: Introductionmentioning
confidence: 99%